2022
DOI: 10.3390/children9091319
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Function in Friedreich’s Ataxia

Abstract: Background: Friedreich's ataxia is an inherited, rare, progressive disorder of children and young adults. It is characterized by ataxia, loss of gait, scoliosis, cardiomyopathy, dysarthria and dysphagia, with reduced life expectancy. Alterations of respiratory dynamics and parameters are frequently observed. However, in the literature there are few, dated studies with small cohorts. Our study aims to make an objective analysis of the respiratory condition of both early and late stage FRDA patients, looking for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In a study examining the change in bilateral diaphragmatic dysfunction on the FVC, the difference was observed between 10%–47% [ 26 ]. In the only study performed on patients with FDRA, no significant change in the standing-to-supine decrease in FVC [ 7 ]. However, we found an average of 8% (4.1%–13.8%) change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study examining the change in bilateral diaphragmatic dysfunction on the FVC, the difference was observed between 10%–47% [ 26 ]. In the only study performed on patients with FDRA, no significant change in the standing-to-supine decrease in FVC [ 7 ]. However, we found an average of 8% (4.1%–13.8%) change.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that sleep-related breathing disorder is more common in individuals with FRDA, and obstructive sleep apnea correlates significantly with disease duration and clinical severity of FRDA [ 6 ]. The only retrospective study examining respiratory involvement in individuals with FDRA; demonstrated varying degrees of impaired respiratory function in the FRDA [ 7 ]. In that study, despite including patients under 18 with a disease duration of less than 15 years, respiratory muscle involvement was found to be 70%.…”
Section: Introductionmentioning
confidence: 99%